Effect of Caffeine on Cognitive Functions - Deepti S Rao; Manasa R.; Hariprasad N.; Prema K.S. (Journal of All India Institute of Speech and Hearing, 1970)
Biocognition is a new and integrated approach to understand the biological basis of highlevel functions including comprehension and use of speech, visual perception and construction, calculation ability, attention, memory, and executive functions in human beings. Cognitive functions such as attention and information processing are reported to improve with the intake of Caffeine, which acts as a psychoactive stimulant drug. Therefore, the present study examined the effects of caffeine on attention and information processing in college students in the age group of 18 to 21 years. Twenty one volunteers from undergraduate college were selected for the study. A series of cognitive tests including Two Choice Reaction Time, Ten-Choice Reaction Time, word reaction time, word recognition time, subtraction tests, statement verification tests, Stroop test series and vigilance tests were conducted on all the participants with the help of Cognispeed software. The reaction time for the responses was recorded in millisecond duration. A pretest-posttest design was adopted to examine the effect of caffeine and therefore, seven among the twenty one participants selected on a random basis were administered 100 milligram caffeine orally in a beverage twenty four hours after the establishment of baseline measures. The cognitive tests were repeated after thirty minutes of caffeine intake. The data obtained on cognitive functions was analyzed. The results showed differences in reaction time between the pretest and posttest measures on specific cognitive functions. The results are discussed in the light of biocognitive perspective.